2015
DOI: 10.1098/rsos.140423
|View full text |Cite
|
Sign up to set email alerts
|

Detection dog efficacy for collecting faecal samples from the critically endangered Cross River gorilla (Gorilla gorilla diehli) for genetic censusing

Abstract: Population estimates using genetic capture–recapture methods from non-invasively collected wildlife samples are more accurate and precise than those obtained from traditional methods when detection and resampling rates are high. Recently, detection dogs have been increasingly used to find elusive species and their by-products. Here we compared the effectiveness of dog- and human-directed searches for Cross River gorilla (Gorilla gorilla diehli) faeces at two sites. The critically endangered Cross River gorilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 31 publications
2
42
0
Order By: Relevance
“…Importantly, TIRM and TIRMpart performed well according to these 3 criteria in both the 3-month and 3-year sampling periods. This is encouraging considering that previous research has emphasized TIRM when using multiple genetic CR approaches to estimate population size (Puechmaille and Petit 2007;Arandjelovic et al 2011Arandjelovic et al , 2015McCarthy et al 2015). Also encouraging was the result that, in contrast to the general pattern for the models overall, TIRM and TIRMpart had higher overall performance in the 3-year versus the 3-month sampling period, with notably narrower confidence intervals in the former.…”
Section: Discussionsupporting
confidence: 59%
“…Importantly, TIRM and TIRMpart performed well according to these 3 criteria in both the 3-month and 3-year sampling periods. This is encouraging considering that previous research has emphasized TIRM when using multiple genetic CR approaches to estimate population size (Puechmaille and Petit 2007;Arandjelovic et al 2011Arandjelovic et al , 2015McCarthy et al 2015). Also encouraging was the result that, in contrast to the general pattern for the models overall, TIRM and TIRMpart had higher overall performance in the 3-year versus the 3-month sampling period, with notably narrower confidence intervals in the former.…”
Section: Discussionsupporting
confidence: 59%
“…They determined that although dogs require greater total financial investment, they have a much higher probability of detection for forest carnivores than either camera traps or hair snares, and if the same effort necessary to achieve a similar high probability of detection is accounted for dogs may be more cost-effective. Conversely, Arandjelovic et al (2015) demonstrated that dogs are faster and found more gorilla scat than people, but the cost per scat found was significantly higher with dogs than with people, and for the same cost searches by humans could collect 7 times more samples, albeit over a much longer period. Understanding the benefits and limitations, particularly the performance and costs of different methods, allows for better comparisons between survey tools.…”
Section: Comparison With Alternative Methodsmentioning
confidence: 93%
“…Summarizing project costs in terms of project objectives (e.g., cost per scat) is interesting (Arandjelovic et al. 2015; Orkin et al. 2016), but for comparative purposes it is perhaps more useful to report in terms of achievement (total project cost, total area surveyed, probability of detection).…”
Section: Evaluation Frameworkmentioning
confidence: 99%
“…Gastrointestinal parasites, which can be detected through noninvasive surveying, may be ideally suited for health monitoring efforts of a primate community (Gillespie, 2006;Howells, Pruetz, & Gillespie, 2011). They are relatively easy to evaluate from fecal samples collected from habituated primate groups, and can also be acquired in the absence of habituation by scat detection dogs or by searching beneath known feeding or resting locations (Arandjelovic et al, 2015;Orkin, Yang, Yang, Yu, & Jiang, 2016). Several long-term research programs have successfully used temporal parasite data to examine ecological perturbations of threatened primate populations (Bakuza & Nkwengulila, 2009;Chapman, Gillespie, & Speirs, 2005;Gillespie & Chapman, 2008;Gillespie, Chapman, & Greiner, 2005).…”
Section: Introductionmentioning
confidence: 99%